Open Literacy: Games, Social Responsibility and Social Innovation: Editorial Introduction to the Special Issue of Cultural Science Journal - Hartley John; Ellis Katie; Leaver Tama (Cultural Science)
This is the Editorial Introduction to the special collection of articles on Open Literacy: Games, Social Responsibility and Social Innovation, which will be published across volumes 11 and 12 of the Journal. The Editorial includes information on the research symposium where these papers were first presented, and biographical details for the contributors.